2014
DOI: 10.1371/journal.pone.0107902
|View full text |Cite
|
Sign up to set email alerts
|

Complex Analysis of Urate Transporters SLC2A9, SLC22A12 and Functional Characterization of Non-Synonymous Allelic Variants of GLUT9 in the Czech Population: No Evidence of Effect on Hyperuricemia and Gout

Abstract: ObjectiveUsing European descent Czech populations, we performed a study of SLC2A9 and SLC22A12 genes previously identified as being associated with serum uric acid concentrations and gout. This is the first study of the impact of non-synonymous allelic variants on the function of GLUT9 except for patients suffering from renal hypouricemia type 2.MethodsThe cohort consisted of 250 individuals (150 controls, 54 nonspecific hyperuricemics and 46 primary gout and/or hyperuricemia subjects). We analyzed 13 exons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
1
38
1
Order By: Relevance
“…Considering the relatively small sample size in this study, the negative result can be explained by the insufficient statistical power. For the other widely reported common variants rs2280205, rs6820230 and rs2276961, no significant effect on hypouricemia or HUA was identified in our samples, which was in accordance with previous reports (Hurba et al, ; Xing et al, ). As for the rare variants, both single locus and aggregation analysis confirmed increased risk for hypouricemia although they had no significant protection against HUA.…”
Section: Discussionsupporting
confidence: 94%
“…Considering the relatively small sample size in this study, the negative result can be explained by the insufficient statistical power. For the other widely reported common variants rs2280205, rs6820230 and rs2276961, no significant effect on hypouricemia or HUA was identified in our samples, which was in accordance with previous reports (Hurba et al, ; Xing et al, ). As for the rare variants, both single locus and aggregation analysis confirmed increased risk for hypouricemia although they had no significant protection against HUA.…”
Section: Discussionsupporting
confidence: 94%
“…Variant p.V282I was previously described relative to the hyperuricemia and gout phenotype [18]. Moreover, in our previous study, which used association analysis together with functional and immunohistochemical characterization of these variants identified in the adult population, we did not find any influence of these allelic variants on expression, subcellular localization, or urate uptake of GLUT9 transporters [19].…”
Section: Discussionmentioning
confidence: 48%
“…This also happened for WDR1, which is adjacent to a urate transporter gene SLC2A9. Although one studies reported no relationship between SCL2A9 variants and hyperuricemia/gout [13], a number of GWAS and functional studies revealed a significant association between SCL2A9 variants and hyperuricemia/gout [1][2][3][4]12]. A previous study showed that epistatic interactions between WDR1 and SLC2A9 regulated serum urate concentrations, suggesting the biological value of epistatic interactions in the pathogenesis of gout [14]..…”
Section: Introductionmentioning
confidence: 99%